IMPLEMENTASI SISTEM INFORMASI MANAJEMEN AKADEMIK BERBASIS TEKNOLOGI INFORMASI DI PERGURUAN TINGGI VOKASI - Mandasari, Okki; Hidayati, Dian; Damayanti, Deasy Lisa (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
An information system is a set of interrelated components in the collection, processing, storage, and dissemination of data and information. The need for accurate information has become a basic need of a university to support policy making, especially information related to student lecture activities. This paper will describe the implementation of an e-Campuz information technology-based academic information system in terms of effectiveness, disadvantages, advantages, and strategies for improving academic services at the Sinar Mas Polytechnic Berau Coal. This paper uses a descriptive qualitative research type. The results show that: 1) e-Campuz has been effective in supporting the implementation of academic activities, 2) the advantages of e-Campuz are that it can accommodate lecture activities and New Student Admission (PMB) activities, 3) the drawbacks of e-Campuz are more on the Student Admissions system. New (PMB) which requires simplification of the display, 4) the strategy to make e-Campuz more effective and efficient is to disseminate information to students and lecturers regarding procedures for using e-Campuz features and the need for simplification of the application. Based on the results of the study it can be concluded that. e-Campuz is a Cloud Computing-based application that has been effective in facilitating the implementation of academic activities at the Simas Berau Polytechnic. The features in the application are quite complete, starting from New Student Admission (PMB), to the academic portal of students and lecturers. E-Campuz is a web-based academic SIM so that it can be accessed easily. The obstacles faced do not come from the application but from the user, in this case the academic staff and prospective new students who are not educated regarding the use of the application.